2008
DOI: 10.1103/physrevlett.101.217401
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Barrierless Auger Recombination in PbSe Nanocrystals: A Pressure-Dependent Study of Transient Optical Absorption

Abstract: We report rates of Auger recombination (AR) in zero-dimensional (0D) PbSe nanocrystals as a function of energy gap (Eg) by using applied hydrostatic pressure to controllably shift E(g) according to the bulk deformation potential. Our studies reveal that the rate of AR in nanocrystals is insensitive to energy gap, which is in contrast with bulk semiconductors where this rate shows exponential dependence on E(g). These measurements represent the first direct experimental evidence that AR in 0D nanomaterials is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 29 publications
6
87
0
Order By: Relevance
“…Here the damping reflects both scattering from the induced disorder as well as coupling of the nanocrystal to the surrounding matrix. A 500-fs decay time for the applied stress is in agreement with prior studies of the ultrafast relaxation of photoexcited carriers in CdSe nanocrystals of this size: electronhole-hole Auger processes lead to sub-picosecond timescale coupling to the lattice typically through hole relaxation without phonon bottleneck effects 38,41,42 .…”
Section: Discussionsupporting
confidence: 73%
“…Here the damping reflects both scattering from the induced disorder as well as coupling of the nanocrystal to the surrounding matrix. A 500-fs decay time for the applied stress is in agreement with prior studies of the ultrafast relaxation of photoexcited carriers in CdSe nanocrystals of this size: electronhole-hole Auger processes lead to sub-picosecond timescale coupling to the lattice typically through hole relaxation without phonon bottleneck effects 38,41,42 .…”
Section: Discussionsupporting
confidence: 73%
“…28 These dynamics reflect physical processes which are important, beyond fundamental interest, for applications in, e.g., photovoltaics and optoelectronics. [15][16][17][18][21][22][23][24][25][26][27]51,52 In Fig. 6, the dependence of the FWM amplitude on 23 is shown on 4.4 nm PbS CQDs for two excitation wavelengths, either resonant with the excitonic ground state ͑upper curves͒ or closer to the first excited state ͑lower curve͒.…”
Section: B Dynamicsmentioning
confidence: 99%
“…With the focus on measuring carrier multiplication [15][16][17][18][21][22][23] and Auger recombination, [24][25][26][27] many recent experiments on carrier dynamics in PbX CQDs have been based on resolving the transient absorption bleaching of the excitonic ground-state transition after pulsed excitation at high photon energies. From these nonresonant pump-probe experiments, it is however difficult to extract the dynamics of the ground-state exciton only since many pathways come into play over similar time scales including carrier relaxation, photoionization, Auger recombination, and exciton redistribution between different energy states.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that (i) spatial-confinement-induced relaxation of the momentum conservation is critical in low-dimensional structures and can eliminate the barrier for activating Auger processes [13,39], and (ii) alloy disorder may enhance Auger impact [17] and break the kconservation [40]. For localization in InGaAs alloy system, therefore, disorder and spatial confinement should be taken into consideration.…”
Section: Discussionmentioning
confidence: 98%
“…The dimensional dependences of Auger impact in semiconductors are interesting: on one hand, designed lowdimensional structure may reduce Auger recombination rate [37,38]; on the other hand, Auger recombination can be enhanced such that strongly depends on the size of localization but not on the exact electronic structures [13,39]. It is demonstrated that (i) spatial-confinement-induced relaxation of the momentum conservation is critical in low-dimensional structures and can eliminate the barrier for activating Auger processes [13,39], and (ii) alloy disorder may enhance Auger impact [17] and break the kconservation [40].…”
Section: Discussionmentioning
confidence: 99%